Somatostatin Neurons in the Mouse Pontine Nucleus Activate GABAA Receptor Mediated Synaptic Currents in Locus Coeruleus Neurons - Garcia DuBar, Selena; Cosio, Daniela; Korthas, Holly; Van Batavia, Jason P.; Zderic, Stephen A.; Sahibzada, Niaz; Valentino, Rita J.; Vicini, Stefano (Frontiers in Synaptic Neuroscience, 2021)
The pontine nuclei comprising the locus coeruleus (LC) and Barrington's nucleus (BRN) amongst others form the neural circuitry(s) that coordinates arousal and voiding behaviors. However, little is known about the synaptic connectivity of neurons within or across these nuclei. These include corticotropin-releasing factor (CRF+) expressing neurons in the BRN that control bladder contraction and somatostatin neurons (SST+) whose role in this region has not been discerned. To determine the synaptic connectivity of these neurons, we employed optogenetic stimulation with recordings from BRN and LC neurons in brain stem slices of channelrhodopsin2 expressing SST or CRF neurons. Optogenetic stimulation of CRF+ BRN neurons of CrfCre;chr2-yfp mice had little effect on either CRF+ BRN neurons, CRF- BRN neurons, or LC neurons. In contrast, in SstCre;chr2-yfp mice light-activated inhibitory postsynaptic currents (IPSCs) were reliably observed in a majority of LC but not BRN neurons. The GABAA receptor antagonist, bicuculline, completely abolished the light-induced IPSCs. To ascertain if these neurons were part of the neural circuitry that controls the bladder, the trans-synaptic tracer, pseudorabies virus (PRV) was injected into the bladder wall of CrfCre;tdTomato or SstCre;tdTomato mice. At 68-72 hours post-viral infection, PRV labeled neurons were present only in the BRN, being preponderant in CRF+ neurons with few SST+ BRN neurons labeled from the bladder. At 76 and 96hr post-virus injection, increased labeling was observed in both BRN and LC neurons. Our results suggest SST+ neurons rather than CRF+ neurons in BRN can regulate the activity of LC neurons.